Overpotentials and Faraday Efficiencies in CO2 Electrocatalysis-the Impact of 1-Ethyl-3-Methylimidazolium Trifluoromethanesulfonate - Neubauer, Sebastian; Krause, Ralf K.; Schmid, Bernhard; Guldi, Dirk Michael; Schmid, Guenter (Advanced Energy Materials, 2016)
The mixtures of room temperature ionic liquid 1-ethyl-3-methylimidazolium trifl uoromethanesulfonate ([EMIM]TFO) and water as electrolytes for reduction of CO2 to CO are reported. Linear sweep voltammetry shows overpotentials for CO2 reduction and the competing hydrogen evolution reaction (HER), both of which vary as a function of [EMIM]TFO concentration in the range from 4 × 10-3 M (0.006 mol%) to 4869 × 10-3 M (50 mol%). A steady lowering of overpotentials up to an optimum for 334 × 10-3 M is identifi ed. At 20 mol% and more of [EMIM]TFO, a signifi cant CO2 reduction plateau and inhibition of HER, which is limited by H2 O diffusion, is noted. Such a plateau in CO2 reduction correlates to high CO Faraday effi ciencies. In case of 50 mol% [EMIM]TFO, a broad plateau spanning over a potential range of 0.58 V evolves. At the same time, the overpotential for HER is increased by 1.20 V when compared to 334 × 10-3 M and, in turn, HER is largely inhibited. The Faraday effi ciencies for CO and H2 formation feature 95.6% ± 6.8% and 0.5% ± 0.3%, respectively, over a period of 3 h in a separator divided cell. Cathodic as well as anodic electrochemical stability of the electrolyte throughout this time period is corroborated in 1 H NMR spectroscopic measurements.
EAM Import::2019-03-08